Penerapan General English dan English For Specific Purposes di Perguruan Tinggi Khususnya pada Pendidikan Vokasi - Rena Juliana; Reni Juliani (VOCATECH: Vocational Education and Technology Journal, 2020)
Abstract The increasing role of English in this era of globalization seems to force us to recognize that English has a great impact on all aspects of life, so learning the English language is a must. Previously, studying English at Indonesian universities was limited to General English or English General Purposes, which became general subjects. However, over time, learning English has been developed specifically for English for Specific Purposes. This study is intended to show how the use of English learning at universities, especially in vocational education, works. In this study, the literature study was chosen as the research method. The literature study shows that the use of General English and English for Specific Purposes in higher education is very different. Where there is no special learning material for teaching General English. The learning material usually contains general knowledge of English. Unlike English for Specific Purposes, where teaching English for Specific Purposes requires special materials that are tailored to the needs of students depending on the subject. Keywords: Use, General English, English for Specific Purposes, University, Vocational Education. __________________________ Abstrak Meningkatnya peran bahasa Inggris di era globalisasi ini seolah memaksa kita untuk mengakui bahwa bahasa Inggris mempunyai pengaruh besar di segala aspek kehidupan sehingga mempelajari bahasa Inggris merupakan hal yang wajib. Sebelumnya di Indonesia, pembelajaran bahasa Inggris di perguruan tinggi hanya sebatas General English atau English for General Purposes yang menjadi mata kuliah umum, namun seiring berjalannya waktu pembelajaran bahasa Inggris dikembangkan lagi secara khusus dalam mata kuliah English for Specific Purposes. Studi ini memiliki tujuan untuk melihat bagaimana penerapan kedua pembelajaran bahasa Inggris tersebut di perguruan tinggi khususnya pada pendidikan vokasi. Studi pustaka dipilih sebagai metode penelitian dalam studi ini. Dari studi kepustakaan tersebut diperoleh hasil bahwa penerapan General English dan English for Specific Purposes di perguruan tinggi sangatlah berbeda antara keduanya. Dimana tidak ada materi pembelajaran khusus terhadap pengajaran General English. Materi pembelajaran biasanya berisikan pengetahuan umum tentang bahasa Inggris. Beda halnya dengan English for Specific Purposes, dimana dalam pengajaran English for Specific Purpose, dibutuhkan materi khusus yang disesuaikan dengan kebutuhan dari mahasiswa sesuai dengan bidang yang mereka ambil. Kata Kunci: Penerapan, General English, English for Specific Purposes, Perguruan Tinggi, Pendidikan Vokasi. __________________________